Narrating Local Wisdom Through Hypertext: A Study on Cultural Values in Digital Short Stories - Juanda, Juanda; Azis, Azis; Djumingin, Sulastriningsih (Universitas Pendidikan Mandalika, 2025)
Local wisdom plays a crucial role in bridging tradition and cultural innovation amid dynamic social change. This study aims to uncover the values of local wisdom embedded in selected hypertext short stories, focusing on themes such as race, nationalism, eugenic norms, cultural stability, education, and the tension between modern life and primitive culture. Employing a qualitative descriptive method within the framework of literary anthropology, this study analyzed four digital short stories: Ngaben Sederhana by I Made Sugianto (2024), Pulang tanpa Kampung Halaman by Artie Ahmad (2024), Laut Mengambil Cintaku by Jemmy Piran (2022), and Ikan Sungai Bejoe by Dul Abdul Rahman (2020). NVivo 14 software was used to conduct thematic coding, identify recurring cultural patterns, and map the interrelationships among thematic categories. The findings reveal dominant representations of community cooperation, respect for diversity, cultural preservation, critiques of social injustice, and the recontextualization of traditional values in modern settings. Notably, the role of indigenous education emerges as vital in transmitting local values and reinforcing cultural identity. Practically, the results offer valuable insights for educators and curriculum developers seeking to integrate culturally relevant content into teaching materials. This research also provides a foundation for future interdisciplinary studies on the role of local wisdom in sustaining cultural heritage in the digital era.